Estado de la restauración activa en áreas degradadas del bosque Piemontano en el cantón Zamora, provincia de Zamora Chinchipe - Ochoa Saez, Luis Miguel (2023)
The active restoration of degraded areas of Piemontano forests is an alternative to contribute with the process of secondary succession in areas of agricultural use in a state of abandonment that are found in this type of ecosystem. The present study of the state of active restoration within the Numbami reserve, located in the Zamora canton, property of Nature and Culture International (NCI), was carried out with the objective of determining the state of the floristic composition, diversity and horizontal structure of the woody component after 11 years of implementation of active restoration. Three permanent plots of 50 × 50 m (0.25 ha) were installed, which were divided into 4 subplots of 625 m2; all individuals ≥ 5 cm in diameter at breast height (DBH) were recorded and tagged. Composition variables (density, dominance, IVI), Shannon diversity and structure (basal area and diametric structure) were determined. 1437 individuals belonging to 65 species were registered, within 47 genera, 27 botanical families. According to the Shannon index, the diversity of species was medium (2.68). The most representative species of the restoration area were; Graffenrieda cucullata, Miconia glaucescens and Miconia astroplocama, species of early stages of secondary succession in Amazonian piedmont forests. The diversity of woody species according to the Shannon index is medium, showing that active restoration contributes to increasing species diversity. The basal area by diameter classes reflects an inverted "J", represented mainly by the great abundance of individuals in the lower classes. The basal area presented a recovery of 16.56 m2/ha-1, compared to the reference forest of 38.6 m2/ha-1, which shows a recovery of approximately 34.1% of the basal area in the period elapsed since its implementation. mainly represented by ephemeral helophyte species. It is concluded that, although active restoration contributes to the increase in specific diversity and the recovery of basal area in degraded areas of Amazonian foothill forests, it is necessary to continue monitoring in order to know if this increase in diversity and basal area is maintained with time in more advanced stages of succession. Keywords: Piemontano forest, active restoration, ecological succession, diversity, conservation.